(3eaJGM GdaGFV aj Yde GdaQGFVs - (3GdaVd Hf CHj GdSYO GdYUjaQj,J (B750 (3g` s ((3eMeO Hf YHO Gddg Hf GdgGOi Hf eMeO Hf Ydi GdeMQGfi s)
(3ChdgG (B:s
(3jHOC HHGH CSHGH GdejQGK s
(3BNQgG (B:s
(3abO UM ddHfJ GdJi YJb fUagG QHY GdeGd hddJi Ydb KdKGgG KdGKI CKeGf GdeGd hdHfJ GdCHf KdGKI CKeGf Je s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJH ahGJMgG HGdSejc YdjgG Jedc HGSe eMeO Hf MSf Hf GdEees
(3HBNQgG fbhd s
(3efgG fbd Yf GdTYQGfi ai cJGHg GdHMQ GdehQhO s
(3hfbd Yf WdMI Hf WdNI GdfYeGfi s
Keywords: (3Yde GdaQGFVs